The contextual role of TNFR family members in CD8+ T‐cell control of viral infections. Issue 1 (15th August 2013) - Wortzman, Michael E.; Clouthier, Derek L.; McPherson, Ann J.; Lin, Gloria H. Y.; Watts, Tania H.
Summary: Immunity to viruses must be tightly controlled to avoid pathology. Receptors and ligands of the tumor necrosis factor (TNF) family play important roles in controlling lymphocyte activation and survival during an immune response. The role of specific TNF receptor (TNFR) family members in antiviral immunity depends on the stage of the immune response and can vary with the virus type and its virulence. Here, we focus on five members of the TNFR family that are prominently expressed on CD8 + T cells during viral infections, namely, 4‐1BB (CD137), CD27, OX40 (CD134), GITR, and TNFR2. 4‐1BB, CD27, OX40, and GITR have primarily prosurvival roles for CD8 + T cells during viral infection, although under some circumstances 4‐1BB, GITR, or CD27 signals can limit immunity. Although TNFR2 can be costimulatory under some circumstances, its main role in CD8 + T‐cell responses during viral infection appears to be in contraction of the response. Several TNF family ligands are being explored as adjuvants for viral vaccines, and agonistic antibodies to TNFR family members are being investigated for immunotherapy of chronic viral infection alone and in combination with checkpoint blockade. Such therapies will require thorough and specific optimization to avoid pathology induced by hyperstimulation of these pathways.